Prawns identification in the Pangkal Tanjung Balam Lake, Siak Hulu Sub-Regency, Kampar - Tania Nurmanita; Windarti Windarti; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Pangkal Tanjung Balam Lake is inhabited by many types of aquatic organism, including prawns. Scientific information of those prawns, however, is almost none. To understand the types of freshwater prawns present in that area, a research has been conducted in March 2018. There were 3 sampling areas, in the upstream (t1), the middle area (t2), and in the downstream (t3). Freshwater prawns sampling were conducted once/week for a month period. Prawns were caught using bamboo traps. Morphometrical and meristical characteristics of the prawns were then analyzed descriptively and the prawns sampled were identified. There were 131 palaemonids prawns captured and they were identified as Macrobrachium. The freshwater prawns species present were consisted of a single species only, namely Macrobrachium mammilodactylus, Thallwitz, 1892 (Palaemonidae). This species characterized by schapocherite length that is shorter than rostrum length, 7-9 teeth in the dorsal and 2-5 teeth in the ventral of rostrum, all segments except fingers with abundant short mammiliform setae. Keywords :Pangkal Tanjung Balam Lake, freshwater prawns, Macrobrachium  mammilodactylus, mammiliform setae